MAGICAL REALISM IN ONE HUNDRED YEARS OF SOLITUDE: FACT, FANTASY AND SOLITUDE = CHỦ NGHĨA HIỆN THỰC HUYỀN ẢO TRONG TRĂM NĂM CÔ ĐƠN: CÁI THỰC, CÁI HUYỀN ẢO VÀ NỖI CÔ ĐƠN - Ngô, Phương Thanh (2021)
The development of mankind history witnesses the decline in reading culture. In this context, the novel One Hundred Years of Solitude by Gabriel García Márquez might be an interesting and charming work for readers to encourage their reading habit and passion for literature. Since there has been little research on this book in Vietnam, this paper was carried out to investigate magical realism used in the novel – a salient writing style of Gabriel García Márquez in particular and Latin American Literature in general. Hopefully, the research would be a source of reference for students and teachers of English as well as literature studies. The findings indicated that magical realism elements regularly appeared in the novel and played an essential role to manifest the theme of solitude. In addition, the paper also emphasised the value of literature in general and One Hundred Years of Solitude in particular, which warned human being of solitude sickness as an existential situation.